2010
DOI: 10.1371/journal.pone.0008395
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Influences Diurnal Variation of Human Time Perception with Prefrontal Activity Change: A Functional Near-Infrared Spectroscopy Study

Abstract: Human short-time perception shows diurnal variation. In general, short-time perception fluctuates in parallel with circadian clock parameters, while diurnal variation seems to be modulated by sleep deprivation per se. Functional imaging studies have reported that short-time perception recruits a neural network that includes subcortical structures, as well as cortical areas involving the prefrontal cortex (PFC). It has also been reported that the PFC is vulnerable to sleep deprivation, which has an influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 66 publications
4
28
0
2
Order By: Relevance
“…Moreover, rats exhibit circadian variations in time perception similar to those that have been demonstrated in humans (Shurtleff et al, 1990). Furthermore, it was recently reported that sleep deprivation influences diurnal variation of time estimation in humans (Soshi et al, 2010). In Drosophila melanogaster, timing of short intervals is disrupted in circadian mutants (Kyriacou and Hall, 1980).…”
Section: Introductionmentioning
confidence: 55%
“…Moreover, rats exhibit circadian variations in time perception similar to those that have been demonstrated in humans (Shurtleff et al, 1990). Furthermore, it was recently reported that sleep deprivation influences diurnal variation of time estimation in humans (Soshi et al, 2010). In Drosophila melanogaster, timing of short intervals is disrupted in circadian mutants (Kyriacou and Hall, 1980).…”
Section: Introductionmentioning
confidence: 55%
“…In the control task, no feedback sound was given to the participants; therefore, it was a simple time-production task as used in a previous NIRS study. 65 Ten trials (with 15-s rest periods between trials) for each task were performed.…”
Section: Cooperative Button-press Taskmentioning
confidence: 99%
“…Recentemente e seguindo esta ideia de revisitar o modelo de regulação circadiana e homeostática do sono de Borbely (1982), Soshi et al (2010) descreveram uma associação entre áreas neurais envolvidas com a regulação do sono e a percepção de tempo, descrevendo como deletérios os efeitos da privação do sono sobre o desempenho.…”
Section: Considerações Finaisunclassified